UPAYA PREVENTIF PENYALAHGUNAAN NARKOBA MELALUI EDUKASI, SOSIALISASI DAN PEMERIKSAAN NARKOBA PADA SISWA/I SMK TI PEMBANGUNAN KAMPUS III - Merdekawati, Fusvita; Abror, Yogi Khoirul; Solihat, M. Firman; Khairunnisa, Syirin Nisrina; Rahmawati, Tia; Dzulhizza, Zaskia Puteri (Poltekkes Kemenkes Bandung, 2025)
Drug abuse among teenagers has become a chronic issue in Indonesia, which is currently in a state of drug emergency. The misuse of narcotics, dangerous drugs, and other addictive substances can cause various negative impacts on users' lives, leading to mental and physical damage, as well as the destruction of social relationships, morals, careers, and finances. The problem of drug abuse among youth is not easy to solve, as it requires collaboration from multiple parties, including the government, police, community members, the media, families, schools, and the teenagers themselves. The main goal of this community service program was to provide students at SMK TI Pembangunan Campus III with a comprehensive understanding of narcotics and their effects on life. The program used a structured method that involved: Pre-test: To assess the students' initial understanding of drugs. Education and Socialization: To provide knowledge and awareness. Urine Screening: As a screening tool for drug use among students. Post-test: To evaluate the increase in understanding after the program. The program successfully increased students' understanding of drugs. This finding strongly suggests that the educational program was effective in achieving its goal. The improvement in understanding was reflected not only in the rise of average scores but also in the consistent improvement among almost every individual student who was measured. These positive results imply that the methods and curriculum used in the program are worth maintaining or even developing further.